Structural, microstructural and electrical properties of vitrium-doped barium titanate for multilayer - Hernández López, Ana María (2018)

(untitled)
Barium titanate (BaTiO3) has attracted the attention for decades both, in the fundamental research field as in industry for device applications. This is a noteworthy ferroelectric material because it has a high ferroelectric activity, dielectric constant and spontaneous polarization (Li, Xu, Chu, Fu, & Hao, 2009) and presents a high resistivity (1010–1012 Ω cm) (Belous, V’yunov, Glinchuk, Laguta, & Makovez, 2008). For the above mentioned, barium titanate has a great potential for technological applications in the electronics industry. In fact, due to its high dielectric constant, low dielectric loss and superior performance at high frequency, one of its most common applications is as the dielectric material for ceramic capacitors (Wang, Chen, Gui, & Li, 2016).